Sprawozdanie z prac archeologicznych prowadzonych na cmentarzysku wczesnośredniowiecznym w Mroczkowie Ślepym, stanowisko 1, gm. Opoczno, woj. Piotrków Trybunalski - Tyszler, Lubomira (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
In all, ten skeleton burials were discovered in the cemetery at Mroczków Ślepy. Bodies are placed in West-East direction with deviation to South, and with heads to West. These were two women graves and eight child graves in infant age I and II. In graves 9 and 10 there appeared stone „protection" which may be attributed to the idea the burial ritual in Mazowsze District, or more widely with the paganchristian stone symbolism. The discovered burials form three rows along North-South line. The burial material represents a typical early-mediaeval inventory: temple bows of II and III types (including one Pomeranian bow), small knives, a ring. The cemetery can be dated back to the second half of 12th and early 13th centuries. It is not a churchyard cemetery with a typically mediaeval lay-out of graves in rows and it occupies a hill-top orea of 1,5 hectare. It is located at the border-point of Żarnów and Skrzynno castellanie s near a mediaeval Russian trade trail leading from Czersko-Grójeckie Mazowsze via Drzewica to Końskie. The studies in the cemetery were conducted during only one season and they were of salvage type. The cemetery is partly destroyed.